Processes controlling mid‐water column oxygen minima over the Texas‐Louisiana shelf. Issue 4 (11th April 2015) - Zhang, Wenxia; Hetland, Robert D.; DiMarco, Steven F.; Fennel, Katja
Abstract We investigate distributions of dissolved oxygen over the Texas‐Louisiana shelf using spatially highly resolved observations in combination with a regional circulation model with simple oxygen dynamics. The observations were collected using a towed, undulating CTD during the Mechanisms Controlling Hypoxia (MCH) program. Mid‐water oxygen minimum layers (dissolved oxygen lower than 3.2 mL L−1) were detected in many transects. These oxygen minimum layers are connected with the bottom boundary layer and follow the pycnocline seaward as a tongue of low oxygen into the mid‐water column. T‐S diagrams highlighting the low oxygen minima in both observations and simulations imply direct connections between low‐oxygen bottom water and the oxygen minimum layer. The dynamics of these oxygen minimum layers in the mid‐water column are examined using a three‐dimensional hydrodynamic model, based on the Regional Ocean Modeling System (ROMS). Convergence within the bottom boundary layer relative to density surfaces is calculated, results show that there is a convergence in the bottom boundary layer at the location where the pycnocline intersects the bottom. Buoyancy advection forced by bottom Ekman transport creates this convergent flow, and the corresponding low‐oxygen intrusion. Similar intrusions of near‐bottom water into the pycnocline are observed in other regions. The presence of hypoxia within the bottom boundary layer in the northern Gulf of Mexico creates a unique situation in which these intrusions are also associated with low dissolved oxygen.